AN ERROR ANALYSIS OF ENGLISH VOICELESS CONSONANT [P], [T], [K] AT SMA SWASTA DHARMA PANCASILA MEDAN - Rahmawati, Rahmawati; Previna, Sri; Sitohang, Meliana Febriyanti; Siagian, Mei Melawati; Bancin, Nolawati br (Universitas Borneo Tarakan, 2019)
The aim of this research is to find the percentage of students’ error in pronounciation of voiceless consonant [p],[t],and [k] and also to find out the dominant error most often made by the first grade of SMA Swasta Dharma Pancasila. This research use qualitative method. The population of this research was the first grade SMA Swasta Dharma Pancasila and the sample was X IIS-1.We only researching 30 students. Then they were given 30 word tests containing English voiceless consonant [p], [t], and [k] to be pronounced and recorded. Recording that have been collected as sources of the data.The results of this study indicate that the level of student error in spoken English [p] and [k] consonants is good with consonant percentages [p] 38.4%, consonants [k] 48.3%, but they are fair in spoken consonant sounds [ t] with a percentage of 59.7%Based on the result of this research, We suggest that the students need to learn and practice more about pronounciation of voiceless consonant [p],[t],and [k] to improve their ability in pronounciation English words. For the teachers,Teacher should give more exercise or practice for students in pronounciation of voiceless consonant [p], [t], [k]. Not only that consonant, but the students must study about all the word of English pronounciation. And the teacher must also learn more about how to pronounce and intonate correctly in teaching words from consonant words.